2004
DOI: 10.1103/physrevb.69.085312
|View full text |Cite
|
Sign up to set email alerts
|

Split-off dimer defects on theSi(001)2×1surface

Abstract: Dimer vacancy (DV) defect complexes in the Si(001)2 × 1 surface were investigated using highresolution scanning tunneling microscopy and first principles calculations. We find that under low bias filled-state tunneling conditions, isolated 'split-off' dimers in these defect complexes are imaged as pairs of protrusions while the surrounding Si surface dimers appear as the usual "bean-shaped" protrusions. We attribute this to the formation of π-bonds between the two atoms of the split-off dimer and second layer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Because the pinning prevents any movement, this force results in compressive or tensile strain to either side of the APB, depending on its direction. This is in good agreement with the observed characteristics of APBs, because strain is known to induce an electronic contrast in silicon 23,24 and can shift bands in both directions depending on whether it is tensile or compressive. 25 We therefore interpret the electronic contrast as a strain-induced band shift in the Si(111)2 × 1 reconstruction.…”
supporting
confidence: 90%
“…Because the pinning prevents any movement, this force results in compressive or tensile strain to either side of the APB, depending on its direction. This is in good agreement with the observed characteristics of APBs, because strain is known to induce an electronic contrast in silicon 23,24 and can shift bands in both directions depending on whether it is tensile or compressive. 25 We therefore interpret the electronic contrast as a strain-induced band shift in the Si(111)2 × 1 reconstruction.…”
supporting
confidence: 90%
“…3(d). Similar steps have been seen on Ni and W contaminated Si(0 0 1) surfaces [28,37]. Apparently, the strain induced by the metal incorporation that induces the DVs on the terraces also alters the step energies, transforming the r-S B steps that dominate on the clean Ge(0 0 1) surface to n-S B steps with a DV adjacent to the step edge.…”
Section: Initial Gold Growth and Bulk Migrationmentioning
confidence: 50%
“…Interestingly, the two B dimers at the ends of the ad-dimer rows appear split and elongated along the island dimer row direction in the unoccupied state image; similar features were also observed at the edges of (1 + 2 + 1) DV complexes in extended terraces [28]. The splitting of the isolated, or ''split-off,'' B dimers at the ends of the islands can be explained by the formation of a p bond between the split-off dimers and the lower trough atoms as suggested by Schofield et al for DV complexes on Si(0 0 1) [28,29]. A model of the tetramer created by this bonding is provided in Fig.…”
Section: Initial Gold Growth and Bulk Migrationmentioning
confidence: 56%
“…We found that such a dimer always hosted the H atom before the transition to the C3 form. Appearance of the dimer is similar to imaging a ''split-off dimer" observed in [17]. It is evident that the C3 defect possesses a kind of asymmetry and an interaction of the H and OH group at the ''dark" reacted dimer also influences the adjacent, formerly H-reacted, dimer.…”
Section: Stm Observationmentioning
confidence: 68%